Islamic English in Indonesia's Digital Culture: A Library Research on Online Islamic Communities - Sri Mulyani; Hanung Triyoko (Universitas Al-Qolam Malang, 2025)
This study examines the role of Islamic English in shaping Indonesia's digital culture, particularly within online Islamic communities. The objective of the research is to explore how Islamic English facilitates digital da’wah, enhances intercultural dialogue, supports informal language learning, and contributes to identity formation in Indonesia's digital spaces. A qualitative approach was employed, analyzing 11 selected articles to identify key themes and trends related to the integration of Islamic English into digital communication. The study finds that Islamic English plays a central role in transforming religious communication by bridging linguistic divides, enabling effective dissemination of Islamic teachings across cultural and geographical boundaries. Additionally, it enhances identity formation among Indonesian youth by providing a tool for self-expression that reflects both local and global Muslim identities. Islamic English also supports informal language learning, particularly in religious and educational contexts, by fostering dual linguistic and cognitive development. The study concludes that Islamic English is a vital element in Indonesia’s digital culture, shaping religious discourse, identity, and informal learning while enhancing the reach of digital da’wah. Keywords: Islamic English, digital da’wah, intercultural dialogue, informal language learning, identity formation